Joining of carbon fibre reinforced polymer (CFRP) composites and aluminium alloys – A review - Pramanik, A.; Basak, A.; Dong, Yu; Sarker, Prabir; Uddin, M.; Littlefair, G.; Dixit, A.; Chattopadhyaya, S. (Pergamon, 2017)
This paper investigates comprehensive knowledge regarding joining CFRP and aluminium alloys in available literature in terms of available methods, bonding processing and mechanism and properties. The methods employed comprise the use of adhesive, self-piercing rivet, bolt, clinching and welding to join only CFRP and aluminium alloys. The non-thermal joining methods received great attention though the welding process has high potential in joining these materials. Except adhesive bonding and welding, other joining methods require the penetration of metallic pins through joining parts and therefore, surface preparation is unimportant. No model is found to predict the properties of jointed structures, which makes it difficult to select one over another in applications. The choice of bonding methods depends primarily on the specific applications. The load-bearing mechanism of bolted joints is predominantly the friction that is the first stage resistance. Hybrid joints performance is enhanced by combining rivets, clinch or bolts with adhesives.